KALINGA STYLE ART OF SOME VAISHNAVITE IMAGES OF JAGANNATHA DHAMA OF ODISHA IN EASTERN INDIA - Mohapatra, Ratnakar; Beruk, Chiranjibi (International Journal of Psychosocial Rehabilitation, 2020)
Jagannath Dhama popularly known as Puri, is famous for its historic antiquities in Odisha of Eastern India. This place is also well-known throughout the world for the celebrated temple of Lord Jagannatha. On the basis of available of a good number of Vaishnavite images, the place of Puri is considered as an important centre of Vaishnavism in Odisha. The worship of Lord Vishnu is very common among the people of Hindu communities of India. Really, a large number of Vaishnavite images of medieval and modern periods are noticed in the different sites of the Puri district. As an important place of Odishan temple art, it is very interesting study for scholars of history particularly art history. The extant Vaishnavite images of the Jagannath Dhama possess the iconographic features of the Odishan classical art of the medieval and early periods. The study of extant Vaishnavite images of the Jagannath Dhama of Odisha is one of the fascinating aspects of the Kalingan school of art of Eastern India. From the artistic point of view, some Vaishnavite images of the different Vaisnavite temples of Jagannath Dhama are very interesting study for the scholars of art history. The aim of this paper is to study the iconographic features along with the religious significance of some important Vaishnavite images of the Jagannatha Dhama of Odisha in detail. Some of the Vaishnavite images of the Jagannatha Dhama of Odisha have to be discussed here are 1. Narasimha of Narasimha temple of the Jagannatha Temple Complex, 2. Nila Madhava of Nila Madhava temple, 3. Three Parsvadevatas of Lord Jagannatha temple, 4. Two Vaishnavite images of Lakshmi temple, 5. Lakshmi- Narasimha of Narasimha temple at Navakalevara Road, 6. Vishnu of Kapala Mochana temple, 7. Vishnu of Beleshvara temple of Belesvara, 8. Sakhi-Gopala of Satyabadi, and 9. Alvarnath of Brahmagiri. All the extant Vaishnavite deities / images of the Jagannatha Dhama are executed by the Kalingan School of artists of Eastern India. Methodologically, both the primary and secondary sources have been used here for the writing of this article.